State Legal Forms of Interaction with Debt Obligations and State Losses - DMYTRYK, Olga O.; KOSTENKO, Yuliia O.; MONAIENKO, Anton O.; RIADINSKA, Valeriia O.; SOLDATENKO, Oksana V. (Journal of Advanced Research in Law and Economics, 2020)
Regulation of financial relations in the state is first and foremost based on an understanding of the allowed extent of freedom of financial transactions. In this regard, of relevance becomes the understanding of what is a limitation or expansion of the freedom of economic thought. The novelty of the study is determined by the fact that financial obligations ultimately become the tasks of state financial regulation. The authors demonstrate that the study should include the task of providing the state with a methodology and a toolkit for handling debt obligations within the state. The secondary objective is to build an understanding that legislation should also be aimed at reducing potential losses. Financial violations of a corruption nature are considered as objects of causing losses. The practical significance of the study lies in the fact that due to the reduction of problematic situations in the legislation, the socio-economic stability of the state as at large increases.